2017
DOI: 10.1017/s0033291717003361
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial functioning among regular cannabis users with and without cannabis use disorder

Abstract: BACKGROUND In the United States, cannabis accessibility has continued to rise as the perception of its harmfulness has decreased. Only about 30% of regular cannabis users develop cannabis use disorder (CUD), but it is unclear if individuals who use cannabis regularly without ever developing CUD experience notable psychosocial impairment across the lifespan. Therefore, psychosocial functioning was compared across regular cannabis users with or without CUD and a non-user control group during adolescence (age 17;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…In this study, recovered individuals described their problems as having developed for multiple reasons, but in particular due to the use of cannabis to cope, because of environmental and social influences, and enjoyment of the positive effects. These perceptions align with research into the etiology of CUD insofar as coping motives for cannabis use have been found to be associated with the development of cannabis use disorders [ 6 , 13 ]; environmental and social influences such as low parental monitoring, high peer group deviance, and cannabis availability have been found to predict cannabis initiation [ 15 ]; and perceived risk of harm has been found to be inversely associated with frequency of cannabis use [ 10 , 12 , 19 ]. Interestingly, we previously reported the responses of this sample to the Marijuana Motives Measure (MMM, [ 27 ]), which indicated that participants most often used cannabis for enhancement motives during their lifetime, followed by social, coping, expansion, and conformity motives [ 29 ].…”
Section: Discussionsupporting
confidence: 62%
“…In this study, recovered individuals described their problems as having developed for multiple reasons, but in particular due to the use of cannabis to cope, because of environmental and social influences, and enjoyment of the positive effects. These perceptions align with research into the etiology of CUD insofar as coping motives for cannabis use have been found to be associated with the development of cannabis use disorders [ 6 , 13 ]; environmental and social influences such as low parental monitoring, high peer group deviance, and cannabis availability have been found to predict cannabis initiation [ 15 ]; and perceived risk of harm has been found to be inversely associated with frequency of cannabis use [ 10 , 12 , 19 ]. Interestingly, we previously reported the responses of this sample to the Marijuana Motives Measure (MMM, [ 27 ]), which indicated that participants most often used cannabis for enhancement motives during their lifetime, followed by social, coping, expansion, and conformity motives [ 29 ].…”
Section: Discussionsupporting
confidence: 62%
“…Approximately 9.5% of US adults report past-year cannabis use 10. Cannabis use disorders (CUDs; ie, cannabis abuse and dependence) are characterised by problems related to cannabis use11 12 and associated with psychiatric and substance use comorbidities, disability and psychosocial problems 13 14. Among US adults, 2.5% report past-year CUDs and 6.3% report lifetime CUDs,13 making CUDs the most prevalent illicit substance use disorder in the USA 15.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, despite symptom attenuation, an individual with PTSD may be vulnerable to developing a CUD. This is particularly problematic given that CUD has been associated with various adverse correlates, including increased rates of psychiatric conditions (Hasin et al, 2016; Kedzior & Laeber, ; Wittchen et al, ), physical health problems (Aldington et al, ; Creane et al, ; Hall & Degenhardt, ), and psychosocial interference (APA, ; Foster et al, ; Leeies, Pagura, Sareen, & Bolton, ), and comorbid PTSD and CUD has been associated with poorer PTSD treatment outcomes, particularly impacting improvements in avoidance and hyperarousal symptoms (Bonn‐Miller, Boden, Vujanovic, & Drescher, ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has linked heavy cannabis use and CUD to increased respiratory difficulties (Aldington et al, ; Hall & Degenhardt, ), cardiovascular dysfunction (Hall & Degenhardt, ), poor oral health (Meier et al, ), cognitive impairment (Creane, Crane, & Mason, ; Hall, ), and reproductive complications (Hall & Degenhardt, ). Cannabis use is also associated with psychosocial impacts such as poor academic performance (Hall & Degenhardt, ), interpersonal and social problems (e.g., greater antisocial and fewer prosocial peers; American Psychiatric Association, ; Foster, Arterberry, Iacono, McGue, & Hicks, ), decreased quality of life (Goldenberg, IshHak, & Danovitch, ), and poorer overall functioning (APA, ). Comorbid PTSD can worsen the aforementioned outcomes (Brady & Clary, ; Pacella, Hruska, & Delahanty, ; Roth, Geisser, & Bates, ), and comorbid PTSD and CUD have been associated with elevated rates of co‐occurring psychiatric conditions (Kevorkian et al, ).…”
Section: Introductionmentioning
confidence: 99%